Studi Literatur Tentang Pengelolaan Tenaga Pendidik dan Kependidikan - Aryana, Mita; Wahyu Ningsih, Sulis; Amelia Widyastuti, Esa; Lestari, Yunita; Fastawa Aqidah, Mutiara; Heru Susanto, Bahtiyar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this study is to explore the implementation and sustainability management of education and to understand efforts made to enhance educational quality in schools. Educational management and administration play a crucial role in improving the quality of educators. The method employed in this research is a qualitative literature review. Literature review is an essential research method used to gather and synthesize information from various relevant sources related to the research topic. In this context, educational management refers to the process of organizing, coordinating, and overseeing educational activities to achieve effective educational goals. Development and coaching in the field of educational staffing are crucial given the advancements in science and technology. Continuous training and development programs are necessary to ensure that the potential and abilities of educators function optimally